SPATIAL DISTRIBUTION OF INVASIVE PLANTS IN BANDUNG, WEST JAVA, INDONESIA - Rahmawati, Rahmawati; Rosleine, Dian (SEAMEO BIOTROP, 2023)
The urban area is a source of invasive plants that enter through human activities such as agriculture and land-use conversion. Studying the invasive plant in urban areas is essential to understanding the city’s ecosystem health condition. Therefore, this study aims to inventory invasive plants, map their distribution, and explain the relationship between land use with the community diversity and species richness of invasive plants in Bandung. The vegetation analysis was performed using line-transect in 22 study sites distributed using a systematic random sampling method in Bandung to observe the plant species composition. The study plots were placed based on the land-use type. The species name, individual number, frequency, and sampling site locations were noted and analyzed to calculate the important value index (IVI) and the invasive species distribution pattern using the principal component analysis (PCA). The dominant invasive species was spatially mapped. Six types of land use were used in this study, i.e., settlements, street green lanes, gardens, paddy fields, urban parks, and urban forests. There were 187 species found in Bandung, which can be categorized into alien invasive species (39%), invasive native plants (25%), non-invasive alien species (18%), non-invasive native species (15%), and unidentified plants (3%). The most common invasive plants found were Eleusine indica (IVI=10.50%), Trimezia martinicensis (IVI=7.22%), and Cyperus rotundus (IVI=6.74%). Based on the plant community similarity index, the study area with the highest similarities were paddy fields with gardens (50.5%), settlements with road lanes (44.4%), urban parks with road lanes (26.2%), and urban forests with road lane (17.5%). PCA showed Swietenia macrophylla as the most common invasive plant found in urban forests, urban parks, and road lanes, with air humidity as the most influencing environmental factor. Trimezia martinicensis is the most common species in the settlement area affected by high air humidity. Bidens pilosa is an invasive plant commonly found on paddy fields, gardens, settlements, road lanes, and urban park edges. This species can easily and rapidly reproduce with a high survival rate. The many invasive plants found in Bandung must be managed to maintain the urban ecosystem’s health.